HEALTH EDUCATION WITH MEDULA (EDUCATIONAL MEDIA) AS AN EFFORT TO INCREASE ADOLESCENT KNOWLEDGE ABOUT REPRODUCTIVE HEALTH - Ningsih, Ratna; Jaya, Herawati; Kumalasari, Intan; Karantina, Karantina; Salsabila, Jihan; Amelia, Jenny; Risanti, Arifah (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2022)
Adolescence is the time when a person goes from child to adult in 10 to 24 years. This period is a worrying time for teenagers when they want to get away from dependence on their parents, feel curious to know more and are very vulnerable to risky behavior. Bina Lestari High School students have never been given counseling on how to maintain adolescent reproductive health (KRR). In order for the reproductive health status of adolescents to be maintained, it is necessary to provide assistance for health and welfare care for adolescents. The purpose of this activity is to increase the knowledge, understanding, behavior and attitudes of adolescents about reproductive health. The health education method used is in the form of counseling and mentoring discussion groups with the snake and ladder game media (MEDULA). The results of the evaluation showed that many Bina Lestari High School students gained increased knowledge after they studied reproductive health through the snake and ladder media, which included understanding reproductive health, reproductive organs, puberty, menstruation, unwanted pregnancy, and abortion, as well as sexual diseases and HIV-AIDS.